บทบาทความเป็นครูกับการสร้างแรงบันดาลใจในห้องเรียนเด็กประถม - ทามนตรี ประภาวดี (Journal of Education Studies, Chulalongkorn University, 2019)
Inspiration to do things comes from within, as well as the need to achieve and accomplish without being pressured or being requested. If a person is motivated to do things when he/she was a child, they are likely to be committed and will not be easily steered away from the target. They are most likely to work through obstacles. Teachers play a very important key in strengthening and inspiring students through the various strategies. At school, teachers need to be observant and develop new techniques and teaching methods, in order to improve and stimulate students effectively.